The Analysis and Review of Danishnama-yi ‘Ala’i (Mola Publication) - FathAli Akbari; Malakeh Pandjoo (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Danishnama-yi ‘Ala’i (The Book of Knowledge for ‘Ala’ al-Dawla) in Persian, Mola publication in 1394, consists of a preface written by Manouchehr Sadoughi Saha, besides four parts; logic, Elme Zirin (Tabiiyyat), Music, and Elme Barin (Theology). This publication does not include any sections of geometry, charts, and arithmetic. The arrangement of the sections of this work (Mola publication) is in contrast to the intended order of Ibn Sina. Because the special taste of Ibn Sina in the Alaii encyclopedia is that Elme Zirin is to be placed before the Elme Barin and mathematical sections; while, in this work (Mola publication) this feature is taken from the encyclopedia and the Elme Barin follows logic and is posed before music and Elme Zirin. Footnotes of Mohammad Moein in the science section of the book_retrieved from the book published by Anjoman Asar-e Meli, Tehran, 1331_contain references that unfortunately in Mola publication are cited falsely and incorrectly, in contrast to the publication of Anjoman Asar-e Meli. The present study seeks to analyze and criticize the weaknesses and strengths of this manuscript.